Attributions and Exchanges: The Effects of Interpersonal Factors on the Diagnosis of Employee Performance - Heneman, Robert L.; Greenberger, David B.; Anonyuo, Chigozie (Academy of Management Journal, 1989)
A study was conducted with 188 supervisors to assess the relationships among supervisory attributions, the exchange relationship between leaders and subordinates, and critical performance incidents. The results indicated that internal, but not external, attributions were significantly related to the leader-member exchange and to critical performance incidents. We discuss the implications of these findings.